PENINGKATAN KETERAMPILAN MENULIS PUISI MENGGUNAKAN PENDEKATAN PEMBELAJARAN KONTEKSTUAL PADA SISWA SMP - Warjayanti, Galina; Susilowati, Endang; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is motivated by the low score of students in learning to write poetry in SMP Negeri 3 Semparuk therefore, the researcher is interested to apply contextual learning approach. This study is devoted to describe the learning process that can improve the skills of writing poetry, student responses, and the results of writing poetry using contextual learning approaches in A class of seven grade students of SMP Negeri 3 Semparuk. The form of this research is qualitative with descriptive method. Data in this research is the process of learning, student responses, and the results of poetry learning. Data collection techniques in this study using test techniques, observation, and documentation.The results showed that writing poetry using contextual learning approaches in students succeeded in improving students' poetry writing skills. The process of writing poetry writing by teachers is very good. Student responses use a good contextual learning approach. The average score of students between the cycles has increased, in the first cycle reached 74.80 and the second cycle reached 82.96. The percentage of students' completeness score among the cycles also increased, that is in the first cycle reached 52% and the second cycle reached 89%.  Keywords: improvement, skill, poetry writing, contextual learning approach.